Correction of Valgus Dislocation of the Radio-Carpal Joint in a Dog through Ligament Reconstruction with Synthetic Wire: an Alternative to Arthrodesis - Garcia, Daniel Cardoso; Mingrone, Larissa Eckmann; da Silva, José Wagner Amador; de Sá, Marcelo Jorge Cavalcanti (Acta Scientiae Veterinariae, 2021)
Background: Radio-carpal dislocations are normally related to situations of trauma and may be treated with open or closed reduction, reconstruction of injured structures or arthrodesis. The treatment aims to eliminate pain, abnormal joint movement and restore member functions, avoiding or minimizing the development of arthrosis. Notwithstanding the literature on the treatment options, few of them explain the restorative technical applications and their evolution in a later postoperative period. The aim of the present report is to discuss extra-articular joint reconstruction with nylon wire in a canine patient with radio-carpal joint dislocation and ligament rupture. Case: A 10-year-old mixed-breed bitch, weighing 10 kg, after an 8-meter fall, received care at Animal Care Barueri Clínica Veterinária. The animal presented left thoracic member functional impotence and radio-carpal joint valgus dislocation, pain and joint swelling. The patient was sedated and medium-lateral and dorso-palmar X-rays of the distal area of the thoracic member were performed, showing radio-carpal dislocation and a slight radiotransparent line in caudal cortical of the middle third of the left radium, possibly related to an incomplete fracture due to compaction. At this point, the choice was for a closed reduction performed by means of traction followed by internal rotation of the distal extremity of the member. An immobilization device was placed using a vinyl splint for 4 days, until the date of the surgery. For the surgical procedure, a dorso-medial access was opened in the left radio-carpal joint, restoring the short radium collateral joint with nylon 0 suture, anchored on 3 pathways opened in the bones (2 pathways in the radium and 1 in the carpo-radial bone), forming one knot. The subcutaneous tissue was closed and sutured using absorbable wire of 2-0 polyglycolic acid. The skin was sutured using nonabsorbable wire of 3-0 nylon. The immediate postoperative X-rays showed the pathways created, conservation of the bone structures and restoration of the anatomic axis of the radio-carpal joint. The member was again immobilized for 70 days and, 30 days after removal of the splint, the animal could already bear load over the member, without lameness. At 10 months after the surgery, the patient performed X-rays of the medium-lateral and dorso-palmar projections, showing absence of the signs of arthrosis or any joint impairment. There was also absence of lameness and pain, however with reduction in joint movement amplitude, with total extension but more limited flexion. Discussion: Through comparison with the literature it was possible to find similarities with the joint injury approach reported, mainly regarding the form of the suture and the clinical alterations observed, such as short radium collateral ligament rupture related to joint valgus deviation. The treatment strategy in the case combined temporary closed reduction of the joint, immobilization, later joint access and restoration with synthetic wire and long-term immobilization. The postoperative results obtained showed favorable evolution, without signs of joint degeneration, pain or lameness. Possible unwanted consequences related to arthrodesis make the options for reconstruction techniques seem more interesting; however, further information of their application and the combination of its variations in a more directed fashion are still required. Understanding the types of injuries, together with the development of research that assess their diagnosis and evolution, may help treatments to show even better perspectives. Keywords: dislocation, joint, radio-carpal, reconstruction, ligament. Título: Correção de luxação valga da articulação rádio-cárpica em um cão através da reconstrução ligamentar com fio sintético: uma alternativa à artrodese Descritores: luxação, articulação, rádio-cárpica, reconstrução, ligamento.